Antioxidant Peptide Derived from Spirulina maxima Suppresses HIF1α-Induced Invasive Migration of HT1080 Fibrosarcoma Cells - Won Suk Kim; Won Kyo Jung; Sun Joo Park (Journal of Chemistry, 2015)
Hypoxia causes the malignant progression of tumor cells; hence, it has been considered a central issue that must be addressed for effective cancer therapy. The initiation of tumor metastasis requires invasive cell migration. Here, we show that an antioxidant peptide derived from Spirulina maxima suppresses hypoxia-induced invasive migration of HT1080 human fibrosarcoma cells. HT1080 cells treated with a hypoxia-inducing agent, CoCl2, exhibited an increase in invasive migration and intracellular reactive oxygen species (ROS), which is associated with an increase in the expression of hypoxia-induced factor 1α (HIF1α) accompanied by the activation of PI3K/Akt and ERK1/2. The inhibition of PI3K/Akt and ERK1/2 with specific inhibitors diminished the CoCl2-induced increase in HIF1α expression and invasive cell migration. Moreover, CoCl2-induced HIF1α expression was associated with an increase in the expression of molecules downstream of β-integrin, such as N-cadherin, vimentin, and β-catenin. Therefore, the S. maxima peptide effectively attenuated the CoCl2-induced ROS generation and downregulated the HIF1α signaling pathway involving PI3K/Akt, ERK1/2, and β-integrin in cells. These results suggest that the S. maxima antioxidant peptide downregulates the HIF1α signaling pathway necessary for hypoxia-induced invasive migration of HT1080 cells by attenuating intracellular ROS. S. maxima peptide may be an effective constituent in antitumor progression products.